Une entreprise de légitimation de la grammaire arabe: : Les Ḫaṣāʾiṣ d'Ibn Ǧinnī - Sibileau, Julien, (Islamic History and Civilization ;, 2025)
The language of Ḫaṣāʾiṣ is reputed to be difficult to access, and the thought of its author relatively opaque. With this book, readers now have a key to penetrate the linguistic thought of one of the most important grammarians in the Arabic grammatical tradition. It shows how Ibn Ǧinnī used the concepts of the episteme of his time to systematize grammatical explanatory reasoning. On reading this book, the reader will also perceive the importance attached by Ibn Ǧinnī to the role played by the speaker in language change, in that the speaker is seen as the true agent (ʿāmil) of his discourse. This work also offers the reader a broader perspective on Ibn Ǧinnī's relationship with the grammatical tradition, as it shows, for example, that most of Ibn Ǧinnī's diachronic reflections are borrowed from one of Sībawayhi's forgotten disciples (180/796): al-Aḫfaš al-Awsaṭ (215/830).